GLUTARIC ACIDEMIA TYPE 1: A CASE REPORT FROM PAKISTAN - Noor, Noshaba; Waseem, Hira (KHYBER MEDICAL UNIVERSITY JOURNAL, 2022)
INTRODUCTION: Glutaric aciduria type 1 is a neurometabolic disorder occurring due to deficient activity of glutaryl-CoA dehydrogenase. Multiple neurotoxic metabolites start accumulating in plasma, CSF and urine which are detected by mass spectrometry. Early new-born screening plays an important role in early diagnosis whereas typical radiographic features and metabolic workup supports the diagnosis. Treatment guidelines have been constructed to prevent acute encephalopathic crisis and remove neurotoxic metabolites from plasma to prevent brain damage, the goal of treatment. CASE PRESENTATION: An eight month old male patient presented with fever, seizures and altered level of consciousness. He was macrocephalic with examination findings suggestive of upper motor neuron lesion. The typical radiologic features suggestive of glutaric aciduria type 1 were noticed in neuroimaging. Workup for inborn error of metabolism confirmed the same. Early treatment was started keeping a metabolic disease consultant on board. The patient was safely discharged from hospital after stabilization and is well till date. CONCLUSION: This case is being reported to emphasize the importance of early diagnosis, timely management and adherence to proper treatment in paediatric patients presenting with metabolic crisis. This can help prevent irreversible damage in patients especially in the ones diagnosed as glutaric aciduria type 1.